The Process of Training in the Higher Education System Foreign Experience of Modernization - A., Iskhakova S. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article analyzes the foreign experience of modernizing the educational process in higher education and reveals the possibilities of its use in Uzbekistan